1996
DOI: 10.1073/pnas.93.14.7042
|View full text |Cite
|
Sign up to set email alerts
|

bcl-2 overexpression reduces apoptotic photoreceptor cell death in three different retinal degenerations.

Abstract: Apoptosis of photoreceptors occurs infrequently in adult retina but can be triggered in inherited and environmentally induced retinal degenerations. The protooncogene bcl-2 is knoWn to be a potent regulator of cell survival in neurons. We created lines oftransgenic mice overexpressing bcl-2 to test for its ability to increase photoreceptor survival. Bcl-2 increased photoreceptor survival in mice with retinal degeneration caused by a defective opsin or cGMP phosphodiesterase. Overexpression of Bcl-2 in normal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(115 citation statements)
references
References 21 publications
3
109
0
3
Order By: Relevance
“…Based on experimental overexpression in transgenic mice, this has so far been demonstrated for lymphoid cells (McDonnell et al, 1989), for neurons of the central nervous system (Martinou et al, 1994), for hepatocytes (Lacronique et al, 1996) and, recently, for retinal photoreceptors (Chen et al, 1996). In this paper we describe transgenic mice which overexpress Bcl-2 under the control of the murine WAP promoter in their lactating mammmary glands.…”
Section: Discussionmentioning
confidence: 93%
“…Based on experimental overexpression in transgenic mice, this has so far been demonstrated for lymphoid cells (McDonnell et al, 1989), for neurons of the central nervous system (Martinou et al, 1994), for hepatocytes (Lacronique et al, 1996) and, recently, for retinal photoreceptors (Chen et al, 1996). In this paper we describe transgenic mice which overexpress Bcl-2 under the control of the murine WAP promoter in their lactating mammmary glands.…”
Section: Discussionmentioning
confidence: 93%
“…The role of Bcl-2 in retina is unclear. Chen et al (1996) showed that in transgenic mice, expression of bcl-2 under the control of an opsin promoter resulted in partial, temporary preservation of photoreceptors in three types of retinal degenerations, whereas other studies have shown no signi®cant reduction in the rate or extent of apoptosis in photoreceptors (Papermaster, 1997). Furthermore, both increases and decreases in bcl-2 levels have been described after various injuries (Montpied et al, 1993;Gillardon et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Despite distinct functions, BcL-2 and BcL-x have both been found to inhibit the release of cytochrome c, which is associated with the activation of caspase 3 from mitochondria. In transgenic mice expressing the Bcl-2 gene with light-damage, and in degenerating rd mice, there is a partial and temporary preservation of the retina, suggesting a role for antiapoptotic members of the Bcl-2 protein family in the survival of retinal neurons (Chen et al, 1996). Thus, these two anti-apoptotic factors seems to be good candidates for mediating FGF2 survival activity in RPE cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al (1996) made transgenic mice bearing a mutated opsin gene that induces an apoptotic degeneration of photoreceptors and crossed them to other transgenic mice expressing bcl-2 under the control of a murine opsin promoter fragment. This cross results in partial and temporary preservation of the rods and cones expressing high levels of bcl-2.…”
Section: Viral Genes and The Genes Of Cell Cycle Progression And Devementioning
confidence: 99%